Analysis of the quality of hospitalization based on the assessment of patients in Lublin, Poland - Opielak, Grzegorz; Zuzak, Tomasz; Kozioł, Maciej; Cyganok, Mikołaj; Piech, Piotr; Szulc, Anna; Jędrych, Marian (Polish Journal of Public Health, 2018)
Introduction. The problem of health care affects every country. The structure and quality of hospitalization in Poland have changed over recent years. The state’s management of a balanced policy is possible prior to the collection of reports allowing to obtain data enabling assessment of changes in the health structure of the population, development of statistical data, as well as implementation and supervision of the National Health Program. Aim. The aim of the study was to evaluate the quality of hospitalization basing on the patients’ assessment of the availability, conditions, course of treatment and contact with hospital staff in the city of Lublin. Material and methods. The material for analysis was data collected from 254 patients. Respondents represented departments of diabetology, rehabilitation and internal diseases. The group consisted of 159 women and 95 men aged 19-84. The interview questionnaire was a research tool. Respondents were asked to assess: accessibility to hospital, efficiency of completing formalities when admitted to the hospital, cleanliness in the room, quality of the gastronomic services and contact with nursing and medical staff. Likert’s 5-point scale was used. Statistical analysis was performed using the software “STATISTICA 10.0”. Results. Most respondents assessed the quality of hospitalization as satisfactory. As many as 99% of respondents assessed contact with doctors as good or very good. Contact with nursing staff was rated as good by 88% of respondents. Conclusions. This study demonstrated good quality of health care in the examined hospital in Lublin. However, it is important to emphasize the need for further research aimed at collecting data on the presented problem.